Legalitas Pembuktian Dalam Persidangan Secara Virtual Ditinjau Dari Hukum Acara Pidana - Idola Putra Hulu (Iuris Studia: Jurnal Kajian Hukum, 2022)
Evidence plays a role in the examination process at court proceedings in criminal cases. Problems that occur are related to the process of evidence before the current trial, where trials of criminal cases are conducted virtually or via teleconference. In the proving process at virtual criminal proceedings, judges are deemed difficult to assess the authenticity of the evidence and evidence submitted by the public prosecutor and legal advisors electronically, considering that judges do not have expertise in technology and information (IT). The authenticity of evidence and evidence will affect the legality of evidence in the criminal justice system. Virtually criminal case trials are regulated in the Regulation of the Supreme Court of the Republic of Indonesia Number 4 of 2020 concerning Electronic Administration and Trial of Criminal Cases in Courts. The contradiction in the application of a virtual trial to the principles of criminal procedure law, namely the principles of oral and direct examination of judges and the principles of open trials for the public. These two principles cannot be fully applied as in conventional criminal proceedings in general, because the application of these principles has a very different atmosphere and situation so that it has obstacles to apply these principles as a whole. Judges in determining the validity of the evidence presented in the process of evidence at the trial of a criminal case virtually requires an expert who has expertise in his field to state the authenticity of the evidence or evidence.